Lithium induced hypercalcemia: an expert opinion and management algorithm - Kovacs, Zoltan; Vestergaard, Peter; W Licht, Rasmus; P V Straszek, Sune; Hansen, Anne Sofie; H Young, Allan; Duffy, Anne; Müller-Oerlinghausen, Bruno; Seemueller, Florian; Sani, Gabriele; Rubakowski, Janusz; Priller, Josef; et al. (International journal of bipolar disorders, 2022)
BACKGROUND: Lithium is the gold standard prophylactic treatment for bipolar disorder. Most clinical practice guidelines recommend regular calcium assessments as part of monitoring lithium treatment, but easy-to-implement specific management strategies in the event of abnormal calcium levels are lacking. METHODS: Based on a narrative review of the effects of lithium on calcium and parathyroid hormone (PTH) homeostasis and its clinical implications, experts developed a step-by-step algorithm to guide the initial management of emergent hypercalcemia during lithium treatment. RESULTS: In the event of albumin-corrected plasma calcium levels above the upper limit, PTH and calcium levels should be measured after two weeks. Measurement of PTH and calcium levels should preferably be repeated after one month in case of normal or high PTH level, and after one week in case of low PTH level, independently of calcium levels. Calcium levels above 2.8 mmol/l may require a more acute approach. If PTH and calcium levels are normalized, repeated measurements are suggested after six months. In case of persistent PTH and calcium abnormalities, referral to an endocrinologist is suggested since further examination may be needed. CONCLUSIONS: Standardized consensus driven management may diminish the potential risk of clinicians avoiding the use of lithium because of uncertainties about managing side-effects and consequently hindering some patients from receiving an optimal treatment.